(untitled) (Jurnal PGSD, 2025)
Innovation that acts as a solution so that education in Indonesia can improve. One solution is to use learning media. For this reason, researchers have carried out focusky-based learning media research. This research uses descriptive quantitative research methods to analyze the effect of using Focusky learning media on the learning outcomes of class III students at Sanggar Guidance Hulu Langat Malaysia. This research took place over four meetings with a one group pretest-posttest design, involving a sample of 10 students. The research results show that the use of focusky media has a significant influence on student learning outcomes. The average pre-test score was 55 with the highest score being 70 and the lowest being 40, while the average post-test score increased to 84 with the highest score being 100 and the lowest being 70. Apart from that, the value of the paired samples test was 0.001 as we know. if the significance level is below 0.05; then it is stated that there is an influence of the test treatment on the results of the pretest and posttest. The use of focusky media also increases student motivation and involvement in the learning process. This research concludes that Focusky learning media is effective in improving learning outcomes and student enthusiasm for learning. Therefore, the use of interactive learning media such as focusky is highly recommended to improve the quality of learning in the classroom.